Thermal stimuli-responsive behavior of pyrene end-functionalized PDMS through tunable P–P interactions - Ha, Heonjoo; Shanmuganathan, Kadhiravan; Fei, Yunping; Ellison, Christopher J. (Journal of Polymer Science Part B-Polymer Physics, 2016)
Pyrene end-functionalized, telechelic poly(dimethyl siloxane) (PDMS) materials were synthesized and their response to different thermal stimuli was evaluated. The incorporation of pyrene end groups introduces strong pi-pi interactions that facilitated a broad range of thermally responsive properties, in some circumstances forming pyrene nanocrystals that serve as physical crosslinks leading to elastic materials. By synthesizing different chain lengths, samples exhibiting a 7 orders of magnitude change in storage modulus in response to thermal stimuli were produced by modifying only the end-groups (0.6 wt % of all polymer segments). Repeated thermal cycling during rheological experiments revealed that pi-pi interaction and crystallization/melting kinetics of pyrene chain-ends plays a key role in their thermal responsiveness. The properties of these materials were tuned by adding free pyrene, neat PDMS, or graphene oxide (GO) nanoparticles, making them attractive for many applications (e.g., tunable damping materials, heat/light sensors, conductive gels, or light repositionable adhesives). For example, nanocomposites containing 1 wt % GO caused the melting temperature for pyrene crystal domains to more than double, and even induced pyrene end-group crystallization in samples that did not exhibit crystals in neat form. It is hypothesized that these features originate from pi-pi interactions between pyrene ends and GO surfaces. (C) 2015 Wiley Periodicals, Inc.